2017
DOI: 10.1007/82_2017_51
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Manipulation of Borrelia Spp.

Abstract: The spirochetes Borrelia (Borreliella) burgdorferi and Borrelia hermsii, the etiologic agents of Lyme disease and relapsing fever, respectively, cycle in nature between an arthropod vector and a vertebrate host. They have extraordinarily unusual genomes that are highly segmented and predominantly linear. The genetic analyses of Lyme disease spirochetes have become increasingly more sophisticated, while the age of genetic investigation in the relapsing fever spirochetes is just dawning. Molecular tools availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 187 publications
(318 reference statements)
0
31
0
Order By: Relevance
“…On the other hand, AA uptake by the spirochete has received much less attention and, not surprisingly, is much more poorly understood. Using a state-of-the-art mutagenesis technique ( 43 , 55 , 56 ) to target OppDF, the energy lynchpin of the Opp permease, we definitively demonstrated that peptides are essential for replication of B. burgdorferi in vitro and in vivo and that the Opp system is the principal if not the only means by which the bacterium can acquire them. Indeed, we saw a direct correlation between the concentration of IPTG used for induction of the NBD domain and spirochete replication in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, AA uptake by the spirochete has received much less attention and, not surprisingly, is much more poorly understood. Using a state-of-the-art mutagenesis technique ( 43 , 55 , 56 ) to target OppDF, the energy lynchpin of the Opp permease, we definitively demonstrated that peptides are essential for replication of B. burgdorferi in vitro and in vivo and that the Opp system is the principal if not the only means by which the bacterium can acquire them. Indeed, we saw a direct correlation between the concentration of IPTG used for induction of the NBD domain and spirochete replication in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the development of diverse molecular tools has enabled investigators to probe and uncover some of the underlying pathogenic mechanisms of the spirochete on a molecular genetic level [1]. These include the use of targeted mutagenesis studies for investigating the role of genes in a tick-animal model in a high-throughput manner [49][50][51][52], the use of the cre-lox recombination system for the deletion of a set of genes on a plasmid [53] and the use of reporter genes including cat gene [54], lacZ [55,56], luc [57,58] and GFP [33,59].…”
Section: Genetic Manipulation Of B Burgdorferimentioning
confidence: 99%
“…Finally, in the case of gene studies where the role of the gene and the protein it encodes has been deduced by any of the above methods, gene complementation in B. burgdorferi includes the use of shuttle vectors and trans-complementation for the introduction of the gene back into the mutant [64][65][66] to see if it restores the wild-type phenotype. However, genetic manipulation of B. burgdorferi has been greatly hampered by a number of limiting factors, including slow growth, low transformation efficiency, loss of plasmids during laboratory cultivation, the limited number of antibiotic markers for research purposes due to the use of antibiotics such as ampicilin and tertracycline being used to treat Lyme disease patients, and the lack of a minimal defined medium [1,67].…”
Section: Genetic Manipulation Of B Burgdorferimentioning
confidence: 99%
See 1 more Smart Citation
“…Technical hurdles have slowed progress in this area. Genetic manipulation of B. burgdorferi is feasible, but the available genetic tools are still limited, and the process remains cumbersome ( 12 , 13 ). Constitutive gene expression is mostly limited to the use of very strong promoters.…”
Section: Introductionmentioning
confidence: 99%